Five-Year Plan for 1957-58 Government of Bihar Finance Department - Planning Commission (Planning Commission, 1957)
The 1957-58 fiscal year fell under India's Second Five-Year Plan (1956-1961), which aimed for rapid industrialization and an increase in national income. The Government of Bihar, like all other Indian states, formulated its annual budget and development plans within the framework of this national plan.
Government of Bihar
Government of Bihar Finance Department
Keywords: General abstract; Electricity schemes; Administration; Receipts from road transport; Schemes; Working expenses; Miscellaneous departments; Industries; Supplies; Capital Outlay; Industrial development